2014
DOI: 10.1158/1535-7163.mct-13-1001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disintegrin–Metalloproteinase ADAM9 in Gastric Cancer Progression

Abstract: Advanced gastric cancer (GC) is one of the most aggressive gastrointestinal malignancies, ADAM (A Disintegrin and Metalloproteinase)-9 is a cell-surface membrane glycoprotein with oncogenic properties that is overexpressed in several cancers. Herein, we investigated the biological mechanism of ADAM9 in the progression, proliferation and invasion of GC. First, we detected ADAM’s expression, processing and protease activity in GC cells. Protease activity was moderately correlated with ADAM9 protein expression, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
2
31
0
2
Order By: Relevance
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, studies have proposed the usage of ADAM9 as a prognostic or a therapeutic marker in various types of cancer. One example is a study conducted using high and low ADAM9-expressing gastric cancer cell lines (15). It was observed that monoclonal antibodies, or small interfering RNA, specifically targeted against ADAM9 could reduce cell proliferation and invasion in high ADAM9-expressing cell lines but not in low ADAM9-expressing cell lines (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the specific ADAMs discussed above, limited evidence suggests that ADAM9, 97,98 ADAM12, 99,100…”
Section: Other Adams Implicated Cancermentioning
confidence: 99%